Pulmonary congestion during exercise stress echocardiography in hypertrophic cardiomyopathy. (14th October 2021) - Palinkas, E.D; Re, F; Torres, M.A.R; Peteiro, J; Cotrim, C; Van De Heyning, C; Agoston, G; D'Alfonso, M.G; Mori, F; De Castro E Silva Pretto, J.L; Sepp, R; Palinkas, A; et al.
Abstract: Background: B-lines detected by lung ultrasound (LUS) indicate pulmonary congestion during exercise stress echo (ESE). Aim: To assess B-lines during ESE in hypertrophic cardiomyopathy (HCM). Methods: We enrolled 110 HCM patients (age 52±16 years, 74 males) referred for ESE (treadmill in 39, semi-supine bicycle in 71 patients) in 10 quality-controlled centers from 8 countries (Belgium, Brazil, Bulgaria, Hungary, Italy, Portugal, Serbia, Spain). ESE assessment included: left ventricular outflow tract gradient (LVOTG); mitral regurgitation (MR, score from 0 to 3); E/e'; systolic pulmonary arterial pressure (SPAP, from tricuspid regurgitant jet velocity); end-diastolic volume (EDV); left atrial volume (LAV). B-lines were assessed by LUS with the 4-site simplified scan, each site scored from 0 (normal A-lines) to 10 (coalescing B-lines). The positivity criterion was a B-line score stress ≥2 points. Results: LUS was feasible in all subjects, with additional scanning and analysis time <1 minute for each stage (rest and peak stress). B-lines were present in 13 patients at rest and in 33 during stress (12 vs 30%, p<0.001). When compared to patients without stress B-lines (Group 2, n=77), patients with B-lines (Group 1) showed higher values of change from rest to stress (Δ) in LVOTG (Group 1= 39±54 vs Group 2= 21±24 mm Hg, p=0.015) and ΔMR grade (Group 1= 0.7±0.8 vs Group 2= 0.1±0.5, p<0.001), more frequent peak stress E/e' ≥15 (Group 1=61% vs Group 2=27%, p=0.007), lower peak EDV (Group 1= 86±35 vs Group 2= 102±33 ml, p=0.039) and higher peak SPAP (Group 1= 60±21 vs Group 2= 39±12 mm Hg, p<0.001): see figure. At multivariable logistic regression analysis, presence of stress B-lines was predicted by ΔMR grade (odds ratio: 3.96, 95% CI 1.46–10.71) and stress E/e' ≥15 (odds ratio: 4.95, 95% CI 1.24–19.70). Conclusion: B-lines are found in about 1 of 10 HCM patients at rest and in 1 of 3 during ESE. Acute backward heart failure during exercise can recognize multiple mechanisms in HCM, and ESE can help to capture this heterogeneity. Funding Acknowledgement: Type of funding sources: None.